2017
DOI: 10.1155/2017/8615086
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rotation Increments on Imaging Performance for a Rotatory Dual-Head PET System

Abstract: For a rotatory dual-head positron emission tomography (PET) system, how to determine the rotation increments is an open problem. In this study, we simulated the characteristics of a rotatory dual-head PET system. The influences of different rotation increments were compared and analyzed. Based on this simulation, the imaging performance of a prototype system was verified. A reconstruction flowchart was proposed based on a precalculated system response matrix (SRM). The SRM made the relationships between the vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…The poor resolution in the direction perpendicular to the detector head has been improved by a 90°-rotation operation. Recently, we further studied the effect of different rotation increments (36°, 45°, 60°and 90°) with the software of Geant4 Application for Tomographic Emission (GATE) v6.2 [19]. The qualitative and quantitative results indicated that the 60 • and 90 • rotation increments had advantages over the other increments in spatial resolution and noise levels, and which one to choose might depend on the distance between the detector heads or the application requirement.…”
Section: Introductionmentioning
confidence: 99%
“…The poor resolution in the direction perpendicular to the detector head has been improved by a 90°-rotation operation. Recently, we further studied the effect of different rotation increments (36°, 45°, 60°and 90°) with the software of Geant4 Application for Tomographic Emission (GATE) v6.2 [19]. The qualitative and quantitative results indicated that the 60 • and 90 • rotation increments had advantages over the other increments in spatial resolution and noise levels, and which one to choose might depend on the distance between the detector heads or the application requirement.…”
Section: Introductionmentioning
confidence: 99%